Effect of hydroxyapatite on the physicochemical characteristics of a gentamicin-loaded monoolein gel intended to treat chronic osteomyelitis - Rasmané Semdé; Réné Flore Gueu Gondi; Bavouma Charles Sombié; B Gérard Josias Yaméogo; Moustapha Ouédraogo (Wolters Kluwer Medknow Publications, 2012)
Many works have demonstrated the real potential of gentamicin-monoolein-water formulations as bioresorbable and sustained-release implants for the local treatment of the chronic osteomyelitis. In order to improve the efficacy of this type of implant, the incorporation of hydroxyapatite, a well-known osteointegrator material, is thought to be an interesting approach. Five formulations incorporating 0, 2.5, 5, 10, and 20% of hydroxyapatite were examined with regard to their physicochemical and in vitro drug release characteristics. The rheological, thermal (differential scanning calorimetric and thermogravimetric diffraction analysis), X-ray diffraction, and dissolution studies have showed that the presence of hydroxyapatite does not dramatically disturb the cubic liquid crystalline structure of the monoolein-water gel and their ability to progressively release the antibiotic. Implant 20% that was capable to release gentamicin sulfate over a period of four weeks without marked burst effect could be used as a more suitable biodegradable delivery system for the local management of chronic osteomyelitis.